(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2019)
Acid mine drainage (AMD) is one of the main environmental issue caused by chemical and bacterial oxidation of pyrite (FeS2) and other sulfite minerals when exposed to atmospheric conditions during mining. In Brazil, AMD occurs in a former uranium mine and contains radionuclides and other elements, which are precipitated from acidic water by liming. Due to the inefficiency of the treatment, contaminants overflow to the water reservoir of Indústrias Nucleares do Brasil – INB in Caldas. The multiplicity of interactions that can occur between the contaminants and the sediments of the reservoir requires a broader approach in order to understand the fixation and/or transport of these elements. In this work the natural remediation approach is reviewed and an initial chemical and radiochemical characterization of the reservoir sediments is presented. Uranium was determined by spectrophotometry, Ra-226, Ra-228 and Pb-210 by gamma spectrometry and zinc by ICP-OES. Twenty-six sediment samples were collected in the reservoir and a bathymetry survey by sonar was performed to determine the thickness of the sediment layer. All the data were processed using the ArcGIS program. To assess the potential mobility and bioavailability of contaminants and to study the role of bacterial sulfate reduction in the immobilization of these contaminants, Acid-volatile sulfide (AVS) analyzes will be performed as a further step.